Вы находитесь на странице: 1из 13

19

19
. (. 18).
() ,
.
:

r = k2 K ' [ A0 ][ Agas ] = keff' [ Agas ]

(1)


:
E

keff'

kT QAcat # RTeff
e [ A0 ],
=
h QAQcat

K =
'

Q A,ads
QA

(2)

H 00 ads

RT

k2 ,

k2 =

keff

#
A cat

kT Q
e
'
K [ A0 ] h Qcat QA,ads
=

0
( Eeff H 0,
ads )

RT

kT QA# cat RT2


e
h Qcat QA,ads

(3)

E2

.
:

19


(3).

( ),
#
E
2
kT QAcat ,vib
k2 =
e RT
h Qcat ,vibQA,ads ,vib

(4)

, :
E

kT RT2
k2 =
e
h

(5)

#
E
kT QAcat ,rot RT2
k2 =
e
1
h

(6)

,
( ,
) ..

19
.
.
.

r = p A k2,i K i [ A0 ](1 A,i )

(7)

.
.

A A + B B + ... P

(8)

r = k Aa Bb ....[ A0 ]a +b...

(9)

a, b.... - .
, .
, o ,
z

.
,
. (8) :

A A + B B + .. 0O P

(10)

.
(9) :

r = k Aa Bb ... Oo .[ A0 ]a +b +...o

(11)

.
() .
, , 2L
R,
( ), .
, [0]:

19

( ! R ,
).
.
.

[(x)], ..
. , .. x
.
[(x)]
. .
, . .
:

) ,
[0], . -

19
. ) , ,
, .
. , ) ,
.
, (
)).

[(x)] = [0]
:

r = S * kchem [0] = 2* R* 2*L *kchem *[0], {/} (12)


.
[(x)].
. ,
,
, .. ,
. ,
, :

r = k *KA *[(x)]* (1-A) [ 0 ]= kchem *[(x)]

(13)

[ 0 ] , k
, KA , (1-A)
.

A <<1
kchem = k *KA * [0]
:

kchem - {/}, r - { /}
dx
:

dr = 2 R *kchem *[(x)] dx

(14)

19
L

r = 2 Rkchem 2 [ A( x) ] dx

(14)

0 L, .. ,
2 , .
) (. )
f.

(14) (12):
L

f =

2 Rkchem 2 [ A( x) ] dx
0

4 Rkchem L [ A0 ]

[ A( x)] dx
0

L [ A0 ]

(15)

f .

[(x)]. :
(I (x) - I (x+dx)) R2 = kchem * [(x)] 2 R dx

(16)

I (x) , {*2/}

( ).
:

19

d [ A( x)] d [ A( x + dx)]
x
x + dx
2
(
)

I
I

R
D
A
(
)

dx
dx
d 2 [ A( x)]
D ( A)
2
dx

2
R =

2
dx R

(17)

D () , {2/}.
, ..
:

d 2 [ A( x)]
D ( A)
2
dx

2
R dx = kchem * [(x)] 2 R dx

(18)

d 2 [ A( x)]
D ( A)
2
dx

R = 2*kchem * [(x)]

(19)

(18)
.)
,

d 2 =

d [ A( x)]
,
A
[ 0]

[ A( x)]
,
[ A0 ]

- :
1
2

2kchem
x

D ( A) R

1
2

2kchem
d =
dx,
D
(
A
)
R

(20)

2kchem 2
d2 =
dx

D ( A) R
(19), :

19

d 2
=
d2

[ A( x)]
d 2 [ A( x)]
=
A0 ]
2kchem 2
[
A
dx
[ 0 ]

D ( A) R

d 2
=
2
d

(21)
()

2k

1
2

chem
=
L,

D ( A) R

. .

. ,
1
2

2kchem
L,
D
(
A
)
R

= ( L) =

( x) =
(21)

=
A
(

x)

L
= () = C1e + C2e-
[ A0 ]

(22)

C1 C2 .

[0]:

[(x )] = [0]

= 0; = [(x)]/ [0] = 1; = 0

(=0) = C1 + C2 = 1

19
- :

x = L, =
d ()/d = 0 = C1e - C2e- = C1e - C2e-
:

C1e = C2e - = (1-C1) e -

e
e
C1 = , C2 =
e +e
e +e
e
e
e + e
( ) = + =
e +e
e +e
e +e

(23)

e x + e x
csh( x) =
2
e x e x
sh( x) =
2
sh( x) e x e x
th( x) =
= x x
csh( x) e + e

e + e csh ( )
( ) = =
e +e
csh ( )

(24)

D (A) >> kchem

19

2k

1
2

chem
L  1,
=

D ( A) R

(25)

, ,
:

D (A) << kchem

2k

1
2

chem
=
L  1,

D
(
A
)
R

(26)


, [A(x)]:

csh ( )
[(x)] = [0] * () = [ A0 ]
= [ A0 ]
csh ( )

x )
L
(27)
csh ( )

csh (

[(x)]
. (14) :

csh x
L
dx
r = 2 Rkchem 2 [ A( x) ] dx = 4 Rkchem [ A0 ]
csh ( )
0
0
L

(28)
: 0 L, , .
- .
!
, :

10

19

4 Rkchem [ A0 ] L

r=
sh x
csh ( )

r=

|
0

4 Rkchem [ A0 ] L
sh ( 0 ) sh ( )

csh ( )

sh (0) = 0

sh () = - sh (- )

r=

4 Rkchem [ A0 ] L

sh ( ) 4 Rkchem [ A0 ] L th ( )
=
csh ( )

(29)


( 13 15 ) :

f =

4 Rkchem [ A0 ] L

th ( )

4 Rkchem [ A0 ] L

th ( )

(30)

, .. ,
:

D() >> kchem,

f =

th( )

f=1,

<<1

e e 1 1 + 1 + 1
=
=
= 1,

e +e
1 + + 1
0

(31)

, , ,
:

11

19

D() << kchem,

f =

th( )

>> 1

e e 1 e 1
=
= 0,
e + e e

(32)

, ,
, , ..

0<f<1
,
(0< f < 1) ( << 1, f 1):

0< f < 1,

keff = 4 RL kchem

th ( )

ln keff = ln kchem + ln {th ( )} ln ( ) + const

(33)

(32) .
.

:

<< 1, f 1
ln keff = ln kchem + const

keff = 4 R L*kchem
(33a)

const
,
, , (33)

>> 1

ln keff = lnkchem - ln + const = lnkchem ln kchem + ln D(A) + const


(34)
const .

12

19
, (34)

d ln keff
dT

d ln kchem 1 d ln kchem 1 Echem

=
2 dT
2 RT 2
dT

(35)

( !)
( , !)

(33)

d ln keff
dT

d ln kchem Echem
=
dT
RT 2

(36)

() ,
! ( (35) (36)).
:

( !) ,
, !

13

Оценить